Immunotherapy With Interferon α11, But Not Interferon Beta, Controls Persistent Retroviral Infection - Schwerdtfeger, Mara; Dickow, Julia; Schmitz, Yasmin; Francois, Sandra; Karakoese, Zehra; Malyshkina, Anna; Knuschke, Torben; Dittmer, Ulf; Sutter, Kathrin (Frontiers in Immunology, 2022)
Type I Interferon (IFNs), including numerous IFNα subtypes and IFNβ, are key molecules during innate and adaptive immune responses against viral infections. These cytokines exert various non-redundant biological activities, although binding to the same receptor. Persistent viral infections are often characterized by increased IFN signatures implicating a potential role of type I IFNs in disease pathogenesis. Using the well-established Friend retrovirus (FV) mouse model, we compared the therapeutic efficacy of IFNα11 and IFNβ in acute and chronic retroviral infection. We observed a strong antiviral activity of both IFNs during acute FV infection, whereas only IFNα11 and not IFNβ could also control persistent FV infection. The therapeutic treatment with IFNα11 induced the expression of antiviral IFN-stimulated genes (ISG) and improved cytotoxic T cell responses. Finally, dysfunctional CD8+ T cells solely regained cytotoxicity after IFNα11 treatment. Our data provide evidence for opposing activities of type I IFNs during chronic retroviral infections. IFNβ was shown to be involved in immune dysfunction chronic infections, whereas IFNα11 had a strong antiviral potential and reactivated exhausted T cells during persistent retroviral infection. In contrast, during acute infection, both type I IFNs were able to efficiently suppress FV replication.